DATA WAREHOUSE UNTUK PENGELOLAAN PENJUALAN PADA PT. LIPPO KARAWACI, TBK. - Steven Lim (SISFOTENIKA, 2012)
Abstract : The purpose of this research is to design a data warehouse in accordance with the requirements of PT. Lippo Karawaci, Tbk. The company is engaged in the field of property ranging from land acquisition through construction and its maintenance. Designing a data warehouse is limited to the sale. The use of data warehouse is expected to support the information needs of executives in business decisions quickly. The method used is the method of analysis and design. Method of analysis was done through literature study and interviews with relevant parties. Design method is done by determining the process, grain, dimensions, facts, measure, and the mapping OLTP to data warehouse, which is followed by physical design. The results of this study is a data warehouse application systems that include data warehousing, OLAP cube, and an application system that is used to access the data warehouse. Implementation of data warehouse has been evaluated by the evaluation results associated with the display, the benefits and accuracy of application data.Keyword : Data warehouse, Cube, Measure, Dimention, Data Transformation Service (DTS)